Language of Signs: A Multimodal Analysis of Celebrity-Endorsed Advertisements on Nigeria’s Social Media - ADEDOJA, Olayiwola Mofoluwalope; TOYINBO, Praise Anuoluwapo; OYINLADE, Morenike Busayo (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
In today’s advertising landscape, celebrity endorsements on social media have become essential, merging linguistic and multimodal elements to craft engaging stories. This study uses a linguistic multimodal analysis framework to explore how language interacts with visual and linguistic components in celebrity-endorsed advertisements on Nigeria’s digital space, specifically, Instagram, Twitter and Facebook. By examining fifteen purposively selected advertisements, the research explores how linguistic strategies — such as word choices, phrase structures, rhetorical techniques and other modes, are employed alongside visual elements to boost persuasion and engage audiences. The theory adopted for the study is Scollon and Scollon’s Geosemiotics of multimodality that considers all available modes of communication. The data was analysed by categorizing emerging patterns in the data and discussing them based on the tenets of multimodal discourse and geosemiotics. The result shows that the combination of linguistic and multimodal elements creates a powerful synergy that enhances the persuasive impact of these advertisements. This research adds valuable insights to the fields of linguistics, media studies, and digital marketing by shedding light on how language operates within multimodal contexts. In conclusion, this study highlights how language used in celebrity-endorsed adverts on social media strategically shapes consumers’ perceptions and reinforces brand identity. Future research could explore cross-cultural variations in linguistic and multimodal strategies to further enrich our understanding of this phenomenon.